Development and Validation of Moral Self-Image Scale (MSIS) - Naeem, Anam (Journal of Peace, Development and Communication, 2022)
Moral Self-Image (MSI) refers to one’s subjective perception of his/her morality. The present research aimed at the development and validation of the moral self-image scale (MSIS) by using a mixed-method approach. 1100 young adults (19-34 years) from different cities of Pakistan (M=27.5, SD=8.5) were recruited. Qualitative exploration (thematic analysis) yielded seven subordinate themes of Moral self-image: integrity, generosity, compassion, forgiveness, social welfare, lawfulness, and tolerance, which were used as conceptual referents for the development of the item pool. Quantitative analyses (factor analyses and construct validity analyses) showed adequate reliability indicators, and evidence of construct and content validity for MSIS. Results also revealed significant differences in the scores of MSI on gender, educational level, and socio-economic status indicating the relevance of these three demographics as strong influencers. The implication of the present research is for students, researchers, organizations, personnel, and recruitment purposes as well as for forensic and personality psychologists.